RIGI, TLR7, and TLR3 Genes Were Predicted to Have Immune Response Against Avian Influenza in Indigenous Ducks - Pal, Aruna; Pal, Abantika; Baviskar, Pradyumna (Frontiers in Molecular Biosciences, 2021)
Avian influenza is a disease with every possibility to evolve as human to human pandemic arising out of frequent mutations and genetic reassortment or recombination of Avian influenza(AI) virus. The greatest concern is that till date no satisfactory medicine or vaccines are available, leading to massive culling of poultry birds causing huge economic loss, and ban on export of chicken products, which emphasise the need develop alternative strategy for control of AI. In the current study we attempt to explore the molecular mechanism of innate immune potential of ducks against common viral diseases including Avian influenza. In the present study, we have characterized immune response molecules as duck TLR3, TLR7, and RIGI and predicted to have potent antiviral activities against different identified strains of Avian influenza through in silico studies (molecular docking). Future exploitation involve immunomodulation with the recombinant protein, transgenic or gene-edited chicken resistant to bird flu.